Variable’s prediction of gap acceptance roundabout capacity model – Critical gap - Majid, Hirsh; Ali, Hezha Mohammed (Innovaciencia, 2023)
Introduction: The research relevance is determined by the assessment of the capacity of roundabouts and their efficiency are extremely important topics in transport engineering research. As road networks are constantly growing in size and complexity, congestion and insufficient flow capacity are becoming serious problems for traffic. The research aims to determine the critical interval at a certain roundabout using several statistical methods and to compare the results obtained by each of them, respectively. Material and Methods: The statistical methods used in the study included the Ruff, Wu, Troutbeck, Ashworth, and standard deviation methods. Results and Discussion: The results of the study show that the difference between the five methods is minimal, although each method has its characteristics. The analysis of the critical interval for the left and right bands showed that different methods may vary in their estimates, but the overall picture remains within acceptable convergence. The difference between the Wu method and the other methods was found to be negligible, except for the Ashworth method, which has a significant difference in the definition of the critical interval. Conclusion: Thus, all five methods can generally be used to calculate the critical interval at roundabouts. However, due to its simplicity and reliability, the Wu method was recommended for use. The practical significance of the study is that the results provide important guidance and information for the design and management of roundabouts. Estimation of the critical spacing is key to determining the optimal traffic flow regime, which affects safety, flow capacity and convenience for drivers.
Keywords: Transport engineering; Traffic flow; Road networks; Critical interval; Congestion